2013
DOI: 10.1089/scd.2012.0451
|View full text |Cite
|
Sign up to set email alerts
|

An Adipoinductive Role of Inflammation in Adipose Tissue Engineering: Key Factors in the Early Development of Engineered Soft Tissues

Abstract: Tissue engineering and cell implantation therapies are gaining popularity because of their potential to repair and regenerate tissues and organs. To investigate the role of inflammatory cytokines in new tissue development in engineered tissues, we have characterized the nature and timing of cell populations forming new adipose tissue in a mouse tissue engineering chamber (TEC) and characterized the gene and protein expression of cytokines in the newly developing tissues. EGFP-labeled bone marrow transplant mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 53 publications
4
49
0
Order By: Relevance
“…13 Also, Lilja et al found that bone marrow-derived precursor cells infiltrate into adipose tissue under inflammation and become mature adipocytes; this further suggests that most of the regeneration cells that take part in adipogenesis come from recipient circulation. 20 Adipose-derived stromal cells have adipogenic ability, [21][22][23][24] and CD34 + adipose precursor cells may play an important role during adipose tissue regeneration. 25 In the threezone theory reported by Yoshimura et al, they point out that the survival of fat graft was largely determined by adipose tissue regeneration after transplantation and the CD34 + cells were very likely to be the seed cells of the adipogenic progress.…”
Section: Figmentioning
confidence: 99%
“…13 Also, Lilja et al found that bone marrow-derived precursor cells infiltrate into adipose tissue under inflammation and become mature adipocytes; this further suggests that most of the regeneration cells that take part in adipogenesis come from recipient circulation. 20 Adipose-derived stromal cells have adipogenic ability, [21][22][23][24] and CD34 + adipose precursor cells may play an important role during adipose tissue regeneration. 25 In the threezone theory reported by Yoshimura et al, they point out that the survival of fat graft was largely determined by adipose tissue regeneration after transplantation and the CD34 + cells were very likely to be the seed cells of the adipogenic progress.…”
Section: Figmentioning
confidence: 99%
“…Inflammation and angiogenesis are closely interrelated, [55][56][57] and adipose angiogenesis is a key mediator in recruiting adipose precursor cells as well as the subsequent adipogenesis. 58,59 However, there was a reduced inflammatory level and larger final volume of adipose tissue in the PCL group compared with the control group in our study.…”
mentioning
confidence: 99%
“…Surgery plays a key role in the angiogenesis and adipogenesis of the tissue-engineering chamber-generated adipose flap by providing necessary trauma/inflammatory conditions. 10,11,15,16 In addition, the flap is subject to changing mechanical forces, leading to the generation of new mitogenic stimuli that promote angiogenesis and adipogenesis. 17 These mechanisms together may explain the growth observed at the early stage in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that not only the space provided by the tissue-engineering chamber but also surgical trauma trigger novel tissue formation. 10,11 Therefore, we speculate that providing rigid support from the body surface to create an in vivo space around the pedicled flap would provide similar tissue regeneration and avoid the foreign-body reaction.…”
mentioning
confidence: 99%